PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN SUMBER PANGAN LOKAL SEBAGAI PRODUK INOVATIF BERNILAI TAMBAH DI DESA BATU MEKAR - Wiliyani, Siti; Maryanti, Sri; Dayani, Rahman; Rahayu, Nila; Dewi, Suprayanti Martia; -, Sri Maryanti; Septiani, Emilia; Sukmana, Febrian Humaidi (Jurnal Pepadu, 2025)
This Community Service Program (PKM) aims to empower the residents of Dusun Prabe, Batu Mekar Village, West Lombok Regency, through the utilization of kolang-kaling (sugar palm fruit) as an innovative raw material for the development of healthy, locally-based functional beverages. Traditionally processed with limited added value, kolang-kaling holds great potential to be transformed into economically valuable products. The program was implemented in stages using participatory and educational approaches, including preparation (local potential survey), functional food concept dissemination, technical training, and business mentoring. The outcome of this initiative is the creation of Yogurt Wedang Kolang-Kaling, a functional drink that combines the probiotic benefits of yogurt with the nutrition and distinctive taste of kolang-kaling and traditional spices. This product not only carries economic value but also promotes the preservation of local wisdom. Practical training significantly enhanced community skills and awareness of entrepreneurship opportunities based on local resources. The participants’ enthusiasm and their initiative to continue production independently reflect the program’s success in fostering economic self-reliance. This innovation is expected to serve as a foundation for the development of sustainable and competitive home-scale enterprises. Thus, this activity demonstrates that local food-based innovations can serve as strategic solutions to holistically improve community welfare